Kinetics of Oxidation of Oxyhaemoglobin by Benzoquinone - B. Patil, Dilip; R. Kakde, Prakash (Asian Journal of Chemistry, 2010)
Kinetics of the oxidation of oxyhaemoglobin by benzoquinone has been studied by spectrophotometrically. The specific rate of reaction is 3.07 × 102 M-1 s-1 at 25 ºC (pH 6). The kinetic parameters such as frequency factor, energy of activation and entropy of activation are found to be 1.206 × 106 s-1, 20.51 kJ mol-1 and -136.79 JK-1 mol-1, respectively. The effect of pH and the probable mechanism for the reaction are also studied.